Prevalence of hypoxemia & its determinates in children with Acute Lower Respiratory infection - Dr Shikha Malik; Dr Poorva Gohiya; Dr Pragati Sisodia (Pediatric Review: International Journal of Pediatric Research, 2015)
Introduction: Acute lower respiratory tract infections (LRTIs), most commonly pneumonia, are one of the major reasons for which children are brought to the hospitals. Effective reduction of mortality due to pneumonia is possible if children suffering from pneumonia are treated appropriately and promptly. Hypoxemia is the most serious manifestation and strong risk factor for mortality among children with acute lower respiratory tract infections. Early detection and treatment of hypoxemia is important in the management of these children. So in our study, we tried to determine prevalence of hypoxemia in children with acute respiratory tract infections.Methods: It was a prospective cross sectional study on 150 children aged 2 months- 60 months with acute respiratory symptoms (<14 days). The children who fulfilled the inclusion criteria were evaluated and examined thoroughly and their data was recorded in a pretested proforma. Statistical analysis was done with IBM SPSS 18.Results: Present study revealed prevalence of hypoxemia to be 35.3% with no significant correlation of age.Conclusion: Hypoxemia is present in almost one third of <5 children admitted with acute LRTIs and it is significantly associated with immediate outcome. Therefore sufficient measures should be employed to detect and manage hypoxemia.